Supporting Network Enabled Capability by extending the Levels of Conceptual Interoperability Model to an interoperability maturity model. (April 2013) - Tolk, Andreas; Bair, Lisa Jean; Diallo, Saikou Y
The North Atlantic Treaty Organization (NATO) Network Enabled Capability (NNEC) addresses technical and cognitive abilities of NATO requiring technical and operational interoperability standards and targets for adaptation. Net-enabled Modeling and Simulation (M&S) can support in all life cycle phases. The paper evaluates the contribution of four example technical activities of NATO conducted by different bodies of the Research and Technology Organization: net-enabled M&S by the Modeling and Simulation Group, semantic interoperability by the Information Systems Technology panel, new command and control concepts by the System Analysis & Studies panel, and human factors for NNEC by the Human Factors & Medicine panel. The results request a framework that included technical and operational aspects as well. The technical challenges can be supported by the Levels of Conceptual Interoperability Model, which is extended to an Interoperability Maturity Model. The operational challenges can be supported by the NNEC Command and Control Maturity Model. Both models are aligned to provide the necessary support to address NATO's technical and cognitive abilities by M&S services.